Crosslinked aromatic polyester resin composition and method for producing the same
Through a dynamic covalent crosslinking method of bond exchange at high temperature, combined with an ester exchange catalyst, a crosslinked aromatic polyester resin composition is formed, which solves the problems of self-adhesion, reforming and self-repairing of aromatic polyester under high temperature conditions, and achieves efficient reprocessing and heat resistance of the material.
Patent Information
- Application Number
- CN202180070051.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-16
- Filing Date
- 2021-10-14
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-10-14
AI Technical Summary
The prior art is difficult to achieve self-adhesion, reforming and self-repairing properties of aromatic polyesters under high temperature conditions, and the heat resistance and chemical resistance of aromatic polyesters are not fully utilized.
By using aromatic polyester as the matrix polymer, a "dynamic" covalent crosslinking method in which bond exchange can be performed at high temperatures is used to form a crosslinked aromatic polyester resin composition in combination with an ester exchange catalyst. The composition has high strength at room temperature and can be reprocessed and achieved bonding and self-healing between films above the bond exchange activation temperature.
It realizes the ability of aromatic polyester resin to soften and re-form at high temperatures, has self-adhesiveness, re-forming and self-repairing properties, and improves the heat resistance and application value of the material.
Smart Images

Figure BDA0004174840890000171 
Figure BDA0004174840890000181 
Figure BDA0004174840890000182
Abstract
Description
Technical Field
[0001] The present invention relates to an aromatic polyester composition and a method for producing the same, which exhibits self-adhesiveness, re-formability and self-repairability under high temperature conditions. More specifically, the present invention relates to an aromatic polyester composition having a stable cross-linked polymer network at room temperature, and the intermolecular bond exchange reaction is activated at high temperature, thereby softening the sample. Background Art
[0002] Crosslinked polyesters formed by curing aromatic polyesters with carboxyl groups on the side chains with epoxy compounds have been used in the field of adhesives and coatings. However, due to the irreversibility of the covalent crosslinking points, they lack adhesion, reshaping, and repairability. On the other hand, films with bond exchange type dynamic crosslinking can be bonded to each other without using an adhesive, and can obtain films with excellent safety performance in which the dissolution of foreign matter and residual solvents caused by the adhesive is suppressed. Furthermore, aromatic polyesters are particularly advantageous for industrial applications due to their excellent heat resistance and chemical resistance.
[0003] There is a report on a cross-linked polyester resin obtained by mixing an aliphatic polyester having a carboxyl group on a side chain, an aliphatic diepoxide having epoxy groups at both ends, and zinc acetate, and then heating and cross-linking the mixture (Patent Document 1).
[0004] There is reported a resin composition obtained by mixing a hydroxyl group-containing thermoplastic resin, an ester bond-containing thermoplastic resin and an ester exchange catalyst, and heating to crosslink the mixture (Patent Document 2).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent document 1: WO2020 / 045439
[0008] Patent Document 2: Japanese Patent Application Publication No. 2020-23591 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] However, although the cross-linked polyester resin of Patent Document 1 considers aliphatic polyesters having carboxyl groups in the molecule as the base polymer, no research has been conducted on aromatic polyester resins. The reason for this is that Patent Document 1 describes a method of synthesizing a polyester precursor having a mercapto group on the side chain by melt polycondensation of a diol component and thiomalic acid of a dicarboxylic acid having a mercapto group on the side chain, and obtaining a polyester resin having a carboxyl group on the side chain by Michael addition reaction of the precursor with acrylic acid. However, in the case of the direct polymerization of dicarboxylic acid and diol, an aromatic dicarboxylic acid having a melting point of 300°C or more and diol are generally subjected to an esterification reaction at a high temperature (e.g., 200 to 240°C) above the boiling point of the diol, and the energy consumption in the polycondensation is large. Furthermore, the melting points of terephthalic acid and isophthalic acid, which are generally used as raw materials for aromatic polyesters, are both above 300°C. In addition, it is difficult to use due to sublimation crystallization. These technical reasons can also be cited. In addition, in Patent Document 2, resin powders of a hydroxyl-containing thermoplastic resin and a ester-bond-containing thermoplastic resin are separately prepared, and after mixing with an ester exchange catalyst, a flat plate is prepared using an injection molding machine. However, this can actually only be achieved using propylene resin, and propylene resin has the problem of low heat resistance.
[0011] The object of the present invention is to provide a cross-linked aromatic polyester resin composition which has been difficult to achieve so far, characterized in that an aromatic polyester is used as a base polymer, and has high strength at room temperature through "dynamic" covalent cross-linking that can undergo bond exchange at high temperatures, and can be reprocessed and achieve adhesion and self-repair between films above the bond exchange activation temperature, and further, due to the presence of an aromatic component, has excellent heat resistance.
[0012] Technical means of solving problems
[0013] The inventors of the present invention have conducted intensive research and found that the above-mentioned problems can be solved by the following features, thereby achieving the present invention. That is, the present invention is constituted as follows.
[0014] A crosslinked aromatic polyester resin composition comprising a crosslinked aromatic polyester resin (C) and an ester exchange catalyst (D) and satisfying the following (1) to (2).
[0015] (1) The crosslinked aromatic polyester resin (C) is a reaction product of an aromatic polyester resin (A) having a carboxyl group on a side chain and an epoxy compound (B).
[0016] (2) When the cross-linked aromatic polyester resin composition is measured by infrared spectrophotometry, the wave number derived from the hydroxyl group is 3200 to 3600 cm -1 The peak absorbance near 3200~3600 ) relative to the wave number 1730cm derived from the ester bond -1 The peak absorbance near 1730) ratio (A 3200~3600 / A 1730 ) is greater than 0.005 and less than 0.038.
[0017] The acid value of the aromatic polyester resin (A) having a carboxyl group on a side chain is preferably 5 mgKOH / g or more and 120 mgKOH / g or less, and the number average molecular weight is preferably 8,000 or more.
[0018] The molar ratio of the epoxy group contained in the epoxy compound (B) to the carboxyl group contained in the aromatic polyester resin (A) having a carboxyl group on the side chain (carboxyl group:epoxy group) is preferably 100:50 to 100:150.
[0019] The number average molecular weight of the epoxy compound (B) is preferably 100 or more and 500 or less.
[0020] The molar ratio of the transesterification catalyst (D) to the carboxyl groups contained in the aromatic polyester resin (A) having carboxyl groups on the side chains (carboxyl groups: transesterification catalyst) is preferably 100:10 to 100:40.
[0021] A method for producing a cross-linked aromatic polyester resin composition comprises the following steps: mixing an aromatic polyester resin (A) having a carboxyl group on the side chain and having an acid value of 5 mgKOH / g to 120 mgKOH / g, an epoxy compound (B) and an ester exchange catalyst (D), and heating to cross-link.
[0022] A self-adhesive, self-repairing material or forming material containing the cross-linked aromatic polyester resin composition.
[0023] Effects of the Invention
[0024] The cross-linked aromatic polyester resin composition of the present invention has high strength at room temperature due to "dynamic" covalent cross-linking that can exchange bonds at high temperatures, and can be reprocessed and bonded between films at a temperature above the activation temperature of bond exchange. Furthermore, the cross-linked aromatic polyester resin composition has re-molding processability, and can be molded and made into a thin film after the cross-linking reaction, and can be used semi-permanently because it can repair damage due to self-healing properties. DETAILED DESCRIPTION
[0025] The crosslinked aromatic polyester resin composition is a resin composition comprising a crosslinked aromatic polyester resin (C) which is a reaction product of an aromatic polyester resin (A) having a carboxyl group on a side chain (hereinafter also referred to as "aromatic polyester resin (A) having a carboxyl group on a side chain" or "polyester resin (A)") and an epoxy compound (B), and an ester exchange catalyst (D).
[0026] <Aromatic polyester resin having carboxyl groups on the side chains (A)>
[0027] The aromatic polyester resin (A) having a carboxyl group on the side chain is a resin having a carboxyl group on the side chain of an aromatic polyester resin. The side chain here may be a structure in which a carboxyl group is present on a branched substituent (e.g., an aliphatic hydrocarbon group, an aromatic hydrocarbon group, an alicyclic hydrocarbon group, etc.) on the main chain of the aromatic polyester resin, or a structure in which a carboxyl group is present directly on the aromatic polyester resin. Preferably, the structure in which a carboxyl group is present directly on the aromatic polyester resin is present.
[0028] The acid value of the polyester resin (A) is preferably 5 mgKOH / g or more. From the perspective of sufficient crosslinking and improved heat resistance, it is more preferably 10 mgKOH / g or more, and further preferably 15 mgKOH / g or more. In addition, the acid value is preferably 120 mgKOH / g or less. From the perspective of being able to suppress the coating film obtained by the crosslinked aromatic polyester resin composition from becoming too hard due to excessive crosslinking density, it is more preferably 110 mgKOH / g or less, and further preferably 100 mgKOH / g or less.
[0029] The polyester resin (A) preferably contains ester bonds and carboxyl groups at multiple points in the molecule. In particular, it is more preferred that the carboxyl groups contain 2 or more points in the molecular chain, more preferably 3 or more points, and even more preferably 4 or more points. The number of carboxyl groups per molecular chain (N COOH ) is not particularly limited, but may be below 50 points, and has no effect even if it is below 30 points.
[0030] The number average molecular weight (Mn) of the aromatic polyester resin (A) having a carboxyl group on the side chain is preferably 8000 or more, more preferably 10000 or more, and even more preferably 12000 or more. In addition, the number average molecular weight is preferably 30000 or less, more preferably 25000 or less, and even more preferably 20000 or less. By setting it within the above range, it becomes easy to control the acid value of the polyester resin (A).
[0031] The glass transition temperature of the polyester resin (A) is preferably -10°C or higher, more preferably 0°C or higher, and further preferably 5°C or higher. The glass transition temperature is preferably 100°C or lower, more preferably 80°C or lower, and further preferably 60°C or lower.
[0032] The aromatic polyester resin (A) having a carboxyl group on the side chain needs to have a side chain (hereinafter also referred to as a branched structure) and an aromatic group in the molecule. In order to make the polyester resin (A) have a branched structure and an aromatic group, it is preferred that the copolymer component as the raw material thereof has a branched structure and an aromatic group. The polyester resin (A) may be (i) obtained by reacting (copolymerizing) a high molecular weight polyol with a chain extender, or (ii) obtained by adding a monomer containing a carboxyl group to a polyester having a reaction site obtained by reacting a polycarboxylic acid component with a polyol component.
[0033] In the case of (i), at least one of the polymer polyol and / or the chain extender may have a branched structure, and the other may have an aromatic group; or one may have both a branched structure and an aromatic group. One polymer polyol may be used alone or in combination of two or more. When two or more polymer polyols are used in combination, one polymer polyol may have a branched structure, and the other may have an aromatic group; or one may have both a branched structure and an aromatic group. In addition, in the case of (ii), at least one of the polyester and / or the addition monomer having a carboxyl group may have an aromatic group, or both may have an aromatic group.
[0034] As a polycarboxylic acid component for an aromatic polyester resin (A) having a carboxyl group on the side chain, an aromatic dicarboxylic acid component is preferably used. As an aromatic dicarboxylic acid component, there is no particular limitation, and examples thereof include: terephthalic acid, isophthalic acid, phthalic anhydride, naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, and 2,2'-biphenyl dicarboxylic acid. In addition, examples thereof include: aromatic dicarboxylic acids having a sulfonic acid group such as sulfoterephthalic acid, 5-sulfoisophthalic acid, 4-sulfophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, and 5-(4-sulfophenoxy)isophthalic acid, and aromatic dicarboxylic acids having a sulfonate group such as their metal salts and ammonium salts. These compounds may be used alone or in combination of two or more. In addition, terephthalic acid, isophthalic acid, and mixtures thereof are particularly preferred from the viewpoint of enhancing the cohesive force of the coating film.
[0035] As other polycarboxylic acid components, there can be mentioned alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid and anhydrides thereof; aliphatic dicarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, dimer acid, and unsaturated bond-containing dicarboxylic acids such as maleic acid, fumaric acid and anhydrides thereof. In addition, hydroxycarboxylic acid compounds having a hydroxyl group and a carboxyl group in the molecular structure such as 5-hydroxyisophthalic acid, p-hydroxybenzoic acid, p-hydroxyphenylethanol, p-hydroxyphenylpropionic acid, p-hydroxyphenylacetic acid, 6-hydroxy-2-naphthoic acid, 4,4-bis(p-hydroxyphenyl)valeric acid, and thiomalic acid having a mercapto group in the molecular structure can also be used.
[0036] As the polyol component used for the aromatic polyester resin (A) having a carboxyl group on the side chain, a diol component is preferred. As the diol component, an aliphatic diol, an alicyclic diol, an aromatic diol or a diol containing an ether bond is preferred.
[0037] Examples of the aliphatic diol include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2-methyl-1,3-propylene glycol, 2-methyl-1,3-butanediol, 1,5-pentanediol, 2,2-dimethyl-1,3-propylene glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,9-nonanediol, 2-ethyl-2-butylpropanediol (DMH), neopentyl glycol hydroxypivalate, dimethylolheptane, and 2,2,4-trimethyl-1,3-pentanediol.
[0038] Examples of the alicyclic diol include 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, tricyclodecanediol, tricyclodecane dimethanol, spiroglycol, hydrogenated bisphenol A, and ethylene oxide adducts and propylene oxide adducts of hydrogenated bisphenol A.
[0039] Examples of aromatic diols include diols obtained by adding 1 to several moles of ethylene oxide or propylene oxide to each of the two phenolic hydroxyl groups of bisphenols, such as terephthalic acid, isophthalic acid, orthophthalic acid, 1,4-phenylene glycol, ethylene oxide adducts of 1,4-phenylene glycol, bisphenol A, ethylene oxide adducts of bisphenol A, and propylene oxide adducts. Specific examples of diol-modified products of aromatic dicarboxylic acids are not particularly limited, and examples include bis(2-hydroxyethyl)terephthalate (BHET) of ethylene glycol-modified products of terephthalic acid, propylene glycol-modified products of terephthalic acid, ethylene glycol-modified products of isophthalic acid, propylene glycol-modified products of isophthalic acid, ethylene glycol-modified products of phthalic acid, and propylene glycol-modified products of phthalic acid. Furthermore, other examples of the diol-modified aromatic dicarboxylic acids include naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, 2,2'-biphenyl dicarboxylic acid, 5-hydroxyisophthalic acid, sulfoterephthalic acid, 5-sulfoisophthalic acid, 4-sulfophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, 5-(4-sulfophenoxy)isophthalic acid, sulfoterephthalic acid, and / or diol-modified aromatic dicarboxylic acids having a sulfonic acid group or a sulfonate group such as metal salts or ammonium salts thereof.
[0040] Examples of the diol containing an ether bond include diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, neopentyl glycol ethylene oxide adduct, and neopentyl glycol propylene oxide adduct.
[0041] These can be used alone or in combination of two or more.
[0042] The polymer polyol component used for the aromatic polyester resin (A) having carboxyl groups on the side chains is preferably a copolymer of the above-mentioned polycarboxylic acid and the above-mentioned polyol component (polymer polyester polyol). In addition, in order to give an acid value to the polymer polyol, it is also preferred to use a trifunctional or higher polycarboxylic acid compound for acid addition.
[0043] Examples of trifunctional or higher polycarboxylic acid components include compounds such as trimellitic acid, trimesic acid, ethylene glycol ditrimellitic anhydride, glycerol trimellitic anhydride, trimellitic anhydride, pyromellitic anhydride (PMDA), oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride (DSDA), 4,4'-(hexafluoroisopropylidene) diphthalic anhydride (6FDA), and 2,2'-bis((dicarboxyphenoxy)phenyl)propane dianhydride (BSAA). On the other hand, examples of trifunctional or higher polyols include compounds such as glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0044] The number average molecular weight (Mn) of the high molecular weight polyol is preferably 1000 or more, more preferably 2000 or more, and even more preferably 3000 or more. The number average molecular weight is preferably 30000 or less, more preferably 25000 or less, and even more preferably 20000 or less.
[0045] The acid value of the polymer polyol is preferably 0.1 mgKOH / g or more, more preferably 0.2 mgKOH / g or more, and further preferably 0.3 mgKOH / g or more. In addition, the acid value is preferably 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, and further preferably 10 mgKOH / g or less.
[0046] The glass transition temperature of the polymer polyol is preferably -10°C or higher, more preferably 0°C or higher, and further preferably 5°C or higher. In addition, the glass transition temperature is preferably 100°C or lower, more preferably 80°C or lower, and further preferably 60°C or lower.
[0047] The chain extender is not particularly limited, but tetracarboxylic dianhydride may be mentioned.
[0048] Tetracarboxylic dianhydride can include: aromatic tetracarboxylic dianhydride, aliphatic tetracarboxylic dianhydride or alicyclic tetracarboxylic dianhydride, preferably aromatic tetracarboxylic dianhydride. Specifically, for example, pyromellitic anhydride (PMDA), oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenyl tetracarboxylic dianhydride (BPDA), 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride (DSDA), 4,4'-(hexafluoroisopropylidene) diphthalic anhydride (6FDA), 2,2'-bis((dicarboxyphenoxy)phenyl)propane dianhydride (BSAA), these can be used alone or in combination of two or more. Pyromellitic anhydride is also preferred.
[0049] As the copolymerization ratio of the polymer polyol and the chain extender, the chain extender is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and further preferably 2 parts by mass or more, relative to 100 parts by mass of the polymer polyol. In addition, the chain extender is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and further preferably 10 parts by mass or less, relative to 100 parts by mass of the polymer polyol.
[0050] Among the aromatic polyester resins (A) having carboxyl groups on the side chains, polyesters containing carboxyl groups at multiple points are preferably used. There are two methods for introducing an acid value into the polyester resin (A).
[0051] As a first method, a method of introducing carboxylic acid into polyester polyol by acid addition after polymerization can be cited. When monocarboxylic acid, dicarboxylic acid, or trifunctional or higher polycarboxylic acid compound is used in acid addition, there is a possibility of molecular weight reduction due to transesterification, so it is preferred to use a compound having at least one carboxylic anhydride group.
[0052] Examples of the carboxylic anhydride include succinic anhydride, maleic anhydride, phthalic anhydride, 2,5-norbornene dicarboxylic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride (PMDA), oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride (DSDA), 4,4'-(hexafluoroisopropylidene) diphthalic anhydride (6FDA), and 2,2'-bis((dicarboxyphenoxy)phenyl)propane dianhydride (BSAA).
[0053] As a second method, a polyester precursor having double bonds at multiple points is obtained by melt polycondensation using a diol-modified aromatic dicarboxylic acid as a diol and maleic acid as a dicarboxylic acid component. This precursor is reacted with, for example, thioglycolic acid to produce an aromatic polyester resin (A) having carboxyl groups at multiple points on the side chain through a Michael addition reaction between the double bond site derived from maleic acid and the mercapto group.
[0054] <Epoxy Compound (B)>
[0055] The epoxy compound (B) is not particularly limited, but preferably is a compound having two or more epoxy groups in the molecule. As the compound having two or more epoxy groups in the molecule (epoxy crosslinking agent), there is no particular limitation as long as it undergoes a curing reaction with the carboxyl group of the polyester resin (A) to perform crosslinking, but preferably is a polyfunctional epoxy compound having several epoxy groups in the same molecule. By using a polyfunctional epoxy compound, the cured coating film obtained from the crosslinked aromatic polyester resin composition can easily form three-dimensional crosslinks, and heat resistance can be improved.
[0056] Examples of the polyfunctional epoxy compound include cresol novolac epoxy compounds, epoxy compounds having a dicyclopentadiene skeleton, and phenol novolac epoxy compounds. These can be used alone or in combination of two or more.
[0057] Furthermore, in addition to the above-mentioned multifunctional epoxy compounds, epoxy compounds containing nitrogen atoms can be used. By using epoxy compounds containing nitrogen atoms in combination, the coating film of the resin composition can be semi-cured by heating at a relatively low temperature, and the effect of suppressing foaming can also be expected, so it is preferred.
[0058] Examples of the nitrogen atom-containing epoxy compound include glycidylamine-type epoxy compounds such as tetraglycidyldiaminodiphenylmethane, triglycidyl-p-aminophenol, tetraglycidylbisaminomethylcyclohexanone, and N,N,N',N'-tetraglycidyl-m-xylene diamine.
[0059] Examples of commercially available products of the nitrogen atom-containing epoxy compound include "TETRAD-X" (trade name) manufactured by Mitsubishi Gas Chemical Corporation and "jER630" (trade name) manufactured by Mitsubishi Chemical Corporation.
[0060] As the epoxy compound (B) used in the present invention, other epoxy compounds may be used in combination. For example, glycidyl ethers such as bisphenol A diglycidyl ether, bisphenol S diglycidyl ether, and brominated bisphenol A diglycidyl ether, glycidyl esters such as hexahydrophthalic acid glycidyl ester and dimer acid glycidyl ester, alicyclic or aliphatic epoxy compounds such as triglycidyl isocyanurate, 3,4-epoxycyclohexyl methyl formate, epoxidized polybutadiene, and epoxidized soybean oil may be used alone or in combination of two or more.
[0061] From the viewpoint of crosslinking density, the number average molecular weight (Mn) of the epoxy compound (B) is preferably 100 to 500, and more preferably 200 to 400.
[0062] <Crosslinked Aromatic Polyester Resin (C)>
[0063] The crosslinked aromatic polyester resin (C) is a reaction product of the polyester resin (A) and the epoxy compound (B). The reaction can be carried out without a solvent or in the presence of an organic solvent.
[0064] The organic solvent is not particularly limited as long as it does not react with the polyester resin (A), the epoxy compound (B) and the crosslinked aromatic polyester resin (C), and examples thereof include: aromatic organic solvents such as toluene and xylene; aliphatic organic solvents such as heptane and octane; ether solvents such as tetrahydrofuran and diethyl ether; and amide solvents such as dimethylformamide and N-methylpyrrolidone. These may be used alone or in combination of two or more.
[0065] The reaction temperature is preferably 80° C. or higher, more preferably 100° C. or higher, and further preferably 120° C. or higher. Also, it is preferably 200° C. or lower, more preferably 180° C. or lower, and further preferably 160° C. or lower.
[0066] The reaction time is preferably 30 minutes or more, more preferably 1 hour or more, and even more preferably 2 hours or more, although it also depends on the reaction temperature. In addition, it is preferably within 10 hours, more preferably within 8 hours, and even more preferably within 5 hours.
[0067] The mixing ratio of the polyester resin (A) and the epoxy compound (B) can be determined based on the functional group molar ratio between the carboxyl group of the side chain of the polyester resin (A) and the epoxy group of the epoxy compound (B). From the viewpoint of crosslinking reaction efficiency, the ratio of the carboxyl group of the polyester resin (A) to the epoxy group of the epoxy compound (B) (carboxyl group: epoxy group) is preferably 100:50 to 100:150 (molar ratio), and more preferably 100:80 to 100:120 (molar ratio).
[0068] <Transesterification Catalyst (D)>
[0069] The ester exchange catalyst (D) is an ester exchange catalyst for the ester group in the polyester resin (A). Through the ester exchange catalyst (D), the cross-linked aromatic polyester resin composition of the present invention becomes a dynamic covalent cross-link capable of bond exchange at high temperature, thereby having high strength at room temperature, and being reprocessable and achieving inter-film adhesion above the ester exchange activation temperature. Furthermore, through the re-formability of the cross-linked aromatic polyester resin composition, forming and film formation after the cross-linking reaction can be achieved, and because damage can be repaired by self-healing properties, it can also be used semi-permanently. The ester exchange activation temperature of the cross-linked aromatic polyester resin composition can be obtained as the softening temperature based on the inflection point of the change in the linear expansion coefficient.
[0070] Examples of the transesterification catalyst (D) include zinc acetate, triphenylphosphine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 1,8-diazabicyclo[5.4.0]undec-7-ene. Among them, zinc acetate is also preferred.
[0071] From the viewpoint of the mechanical strength of the polyester resin (A) and the uniformity of the sample, the amount of the transesterification catalyst (D) is preferably 10 to 40 mol parts, more preferably 15 to 30 mol parts, based on 100 mol parts of carboxyl groups of the polyester resin (A).
[0072] <Crosslinked Aromatic Polyester Resin Composition>
[0073] The crosslinked aromatic polyester resin composition is a composition containing the crosslinked aromatic polyester resin (C) and the transesterification catalyst (D).
[0074] The wavelength of 1730 cm-1, which is the origin of the ester bond, is measured by infrared spectrophotometry. -1 The peak absorbance near 1730 ), the wave number of hydroxyl group is 3200~3600cm -1 The peak absorbance near 3200~3600 ) ratio (A 3200~3600 / A 1730 ) is 0.005 or more and 0.038 or less. From the perspective of improving self-repairing properties, reshaping properties, and damage repair properties, the ratio (A 3200~3600 / A 1730 ) is preferably 0.007 or more, more preferably 0.01 or more. 3200~3600 / A 1730 ) is preferably 0.035 or less, and more preferably 0.03 or less. The infrared spectrophotometric method is carried out as described in the examples.
[0075] An example of a method for producing a cross-linked aromatic polyester resin composition is shown. The cross-linked aromatic polyester resin composition can be obtained by mixing a polyester resin (A), an epoxy compound (B) and an ester exchange catalyst (D), heating, and performing a cross-linking reaction via an epoxy ring-opening reaction. The order of mixing the polyester resin (A), the epoxy compound (B) and the ester exchange catalyst (D) is not particularly limited, but it is preferred to first mix the polyester resin (A) and the epoxy compound (B), then add the ester exchange catalyst (D), and perform a cross-linking reaction.
[0076] The softening temperature of the crosslinked aromatic polyester resin composition is preferably 100° C. or higher, more preferably 110° C. or higher, and further preferably 120° C. or higher. The upper limit of the softening temperature is not particularly limited, but may be 300° C. or lower industrially, and may be 250° C. or lower.
[0077] When the crosslinked aromatic polyester resin composition is heated, the temperature at which the weight is reduced by 5% is 230° C. or higher, preferably 250° C. or higher, more preferably 280° C. or higher, and further preferably 300° C. or higher. The upper limit of the 5% weight reduction temperature is not particularly limited, but industrially it may be 500° C. or lower, and even 450° C. or lower. The 5% weight reduction temperature can be used as an indicator of heat resistance.
[0078] The shape of the molded product composed of the cross-linked aromatic polyester resin composition can be various, but from the viewpoint of maintaining a sufficient contact area, a film shape is preferred. That is, the cross-linked aromatic polyester resin composition of the present invention can be used as a film-shaped adhesive, and can be used as an adhesive between resin films, between metal foils, between resin films and metal foils, etc. Examples of the resin film include: polyimide film, polyester film, PET film, etc. Examples of the metal foil include: copper foil, silver foil, gold foil, etc. The adhesiveness of the cross-linked aromatic polyester resin composition can be evaluated based on the 90° peel strength shown in the examples.
[0079] The crosslinked aromatic polyester resin composition can undergo bond exchange by heating to a temperature higher than the ester exchange activation temperature. Therefore, when the crosslinked aromatic polyester resin composition is used as an adhesive material, the adhesive can be easily peeled by heating the adhesive to a temperature higher than the ester exchange activation temperature. Thus, the crosslinked aromatic polyester resin composition can be used as a material for a stick-and-peel repair adhesive. The peelability of the crosslinked aromatic polyester resin composition when heated to a high temperature can be evaluated based on the 90° peel strength when heated as shown in the Examples.
[0080] The crosslinked aromatic polyester resin composition can be used as a laminate. Since the crosslinked aromatic polyester resin composition has heat resistance, for example, a film made of the crosslinked aromatic polyester resin composition is attached to a resin molded body and a metal molded body for bonding, and the heat resistance of the resin molded body and the metal molded body can be improved by lamination. The effect as a laminate can be evaluated by the solder heat resistance shown in the examples.
[0081] The crosslinked aromatic polyester resin composition is difficult to dissolve even when immersed in a solvent (particularly an organic solvent), and thus has excellent solvent resistance. Therefore, the crosslinked aromatic polyester resin composition can be suitably used as, for example, a laminate material.
[0082] The crosslinked aromatic polyester resin composition has good storage stability at room temperature. That is, the gel fraction hardly changes even when stored at a predetermined temperature for a certain period of time. In addition, even when stored at a predetermined temperature for a certain period of time, the composition exhibits the same degree of softening behavior as before storage.
[0083] The crosslinked aromatic polyester resin composition can be used as a main component of a self-adhesive, a self-healing material or a molding material.
[0084] As the self-repairing material, a material such as a coating material can be used.
[0085] The crosslinked aromatic polyester resin composition is useful as a molding material because of its excellent molding processability and extrusion moldability. For example, it can be used as a material for 3D printing and a material for a linear molded body.
[0086] In addition, the cross-linked aromatic polyester resin composition can be used as a material for a network structure. A network structure is a structure in which a portion of linear shaped bodies are connected to each other. The network structure can be produced by melting the cross-linked aromatic polyester resin composition, discharging the melt from a nozzle, and solidifying the discharged material while welding it.
[0087] The content of the crosslinked aromatic polyester resin composition in the solid content of the self-adhesive, self-healing material or molding material is preferably 60 mass % or more, more preferably 80 mass % or more, further preferably 90 mass % or more, and may be 100 mass %.
[0088] This application claims the benefit of priority based on Japanese Patent Application No. 2020-174488 filed on October 16, 2020. The entire contents of the specification of the above-mentioned Japanese Patent Application No. 2020-174488 are incorporated herein by reference.
[0089] Example
[0090] In order to further illustrate the present invention in detail, the following examples and comparative examples are given, but the present invention is not limited to the following examples. It should be noted that each measured value recorded in the examples and comparative examples is measured by the following method. In addition, unless otherwise specified, "part" means "part by mass" and "mole" means "part by mole".
[0091] Polymerization Example of High Molecular Polyol (A1-1)
[0092] In a reaction vessel equipped with a stirrer, a thermometer, and a cooler for distillation, 30 mol parts of terephthalic acid, 69 mol parts of isophthalic acid, 1 mol part of trimellitic anhydride, 15 mol parts of 2-methyl-1,3-butanediol, 85 mol parts of 1,6-hexanediol, and 0.2 mol parts of tetrabutyl titanate were added, and the temperature was slowly raised to 250°C, and the distilled water was discharged out of the system while the esterification reaction was carried out. After the esterification reaction was completed, the temperature was raised to 250°C while the initial polymerization was carried out while the pressure was slowly reduced to 10 mmHg, and the post-polymerization was further carried out at 1 mmHg or less until the specified torque was reached. After that, the pressure was returned to normal pressure under a nitrogen atmosphere, and 1 mol part of trimellitic anhydride was added, and the reaction was carried out at 220°C for 30 minutes to obtain a polymer polyol (A1-1). The composition and characteristic values of the polymer polyol (A1-1) obtained in this way are shown in Table 1, and various measurement and evaluation items were measured according to the methods described below.
[0093] Polymerization example of high molecular weight polyol (A1-2)
[0094] In a reaction vessel equipped with a stirrer, a thermometer, and a cooler for distillation, 50 moles of terephthalic acid, 50 moles of isophthalic acid, 55 moles of ethylene glycol, 45 moles of 2,2-dimethyl-1,3-propanediol, and 0.2 moles of tetrabutyl titanate were added, and the temperature was slowly raised to 250°C, and the distilled water was discharged out of the system while the esterification reaction was carried out. After the esterification reaction was completed, the temperature was raised to 250°C while the initial polymerization was carried out while the pressure was slowly reduced to 10 mmHg, and further, the post-polymerization was carried out below 1 mmHg until the torque reached the specified value, thereby obtaining a high molecular polyol (A1-2). The composition of the high molecular polyol (A1-2) obtained in this way and its characteristic values are shown in Table 1, and various measurement and evaluation items were carried out according to the methods described below.
[0095] Polymerization example of high molecular weight polyol (A1-3)
[0096] In a reaction vessel equipped with a stirrer, a thermometer, and a cooler for distillation, 50 mol parts of terephthalic acid, 49 mol parts of isophthalic acid, 1 mol part of trimellitic anhydride, 83 mol parts of 2-methyl-1,3-butanediol, 17 mol parts of 1,4-butanediol, and 0.2 mol parts of tetrabutyl titanate were added, and the temperature was slowly raised to 250°C, and the distilled water was discharged out of the system while the esterification reaction was carried out. After the esterification reaction was completed, the temperature was raised to 250°C while the initial polymerization was carried out while the pressure was slowly reduced to 10 mmHg, and the post-polymerization was further carried out at 1 mmHg or less until the torque reached the specified value. After that, the pressure was returned to normal pressure under a nitrogen atmosphere, and 1 mol part of trimellitic anhydride was added, and the reaction was carried out at 220°C for 30 minutes to obtain a polymer polyol (A1-3). The composition and characteristic values of the polymer polyol (A1-3) obtained in this way are shown in Table 1, and various measurement and evaluation items were measured according to the methods described below.
[0097] Polymerization example of high molecular weight polyol (A1-4)
[0098] In a reaction vessel equipped with a stirrer, a thermometer, and a cooler for distillation, 40 mol parts of terephthalic acid, 39 mol parts of isophthalic acid, 20 mol parts of adipic acid, 1 mol part of trimellitic anhydride, 58 mol parts of 2-methyl-1,3-butanediol, 42 mol parts of 1,4-butanediol, and 0.2 mol parts of tetrabutyl titanate were added, and the temperature was slowly raised to 250°C, and the distilled water was removed from the system while the esterification reaction was carried out. After the esterification reaction was completed, the temperature was raised to 250°C while the initial polymerization was carried out while the pressure was slowly reduced to 10 mmHg, and the post-polymerization was further carried out at 1 mmHg or less until the specified torque was reached. After that, the pressure was returned to normal pressure under a nitrogen atmosphere, and 1 mol part of trimellitic anhydride was added, and the polymer polyol (A1-4) was obtained by reacting it at 220°C for 30 minutes. The composition and property values of the high molecular weight polyol (A1-4) obtained in this manner are shown in Table 1. Various measurement and evaluation items were performed in accordance with the methods described below.
[0099] Polymerization example of high molecular weight polyol (A1-5)
[0100] In a reaction vessel equipped with a stirrer, a thermometer, and a cooler for distillation, 30 mol parts of terephthalic acid, 64 mol parts of isophthalic acid, 5 mol parts of sebacic acid, 1 mol part of trimellitic anhydride, 28 mol parts of 2-methyl-1,3-butanediol, 55 mol parts of 1,4-butanediol, 17 mol parts of 1,4-cyclohexanedimethanol, and 0.2 mol parts of tetrabutyl titanate were added, and the temperature was slowly raised to 250°C, and the distilled water was removed from the system while the esterification reaction was carried out. After the esterification reaction was completed, the temperature was raised to 250°C while the initial polymerization was carried out while the pressure was slowly reduced to 10 mmHg, and the post-polymerization was further carried out at 1 mmHg or less until the specified torque was reached. After that, the pressure was returned to normal pressure under a nitrogen atmosphere, and 1 mol part of trimellitic anhydride was added, and the polymer polyol (A1-5) was obtained by reacting it at 220°C for 30 minutes. The composition and property values of the high molecular weight polyol (A1-5) obtained in this manner are shown in Table 1. Various measurement and evaluation items were performed in accordance with the methods described below.
[0101] As the high molecular weight polyol (T5652), polycarbonate diol "T5652" (number average molecular weight: 2000) manufactured by Asahi Kasei Corporation was used.
[0102] Synthesis Example of Aromatic Polyester Resin Having Carboxyl Groups on Side Chains (A-1)
[0103] Into a reaction vessel equipped with a stirrer, a thermometer, and a reflux tube, 80 parts of a high molecular weight polyol (A1-1), 20 parts of a high molecular weight polyol (A1-2), 2.6 parts of pyromellitic anhydride, and 100 parts of toluene were added, and the mixture was dissolved in toluene while slowly heating to 80°C. After the dissolution was completed, 0.05 parts of triethylamine as a reaction catalyst was added, and the mixture was slowly heated to 105°C to react for 24 hours. After the completion of the reaction was confirmed by IR (infrared spectroscopy analysis), the mixture was diluted with 54 parts of toluene to obtain a solution having a solid content concentration of 40% of the aromatic polyester resin (A-1) having a carboxyl group on the side chain. The composition of the aromatic polyester resin (A-1) having a carboxyl group on the side chain thus obtained and its characteristic values are shown in Table 2.
[0104] Synthesis Example of Aromatic Polyester Resin Having Carboxyl Groups on Side Chains (A-2)
[0105] Into a reaction vessel equipped with a stirrer, a thermometer, and a reflux tube, 80 parts of a high molecular weight polyol (A1-3), 20 parts of a high molecular weight polyol (A1-2), 2.6 parts of pyromellitic anhydride, and 100 parts of toluene were added, and the mixture was dissolved in toluene while slowly heating to 80°C. After the dissolution was completed, 0.05 parts of triethylamine as a reaction catalyst was added, and the mixture was slowly heated to 105°C to react for 24 hours. After the completion of the reaction was confirmed by IR, the mixture was diluted with 54 parts of toluene to obtain a solution having a solid content concentration of 40% of the aromatic polyester resin (A-2) having a carboxyl group on the side chain. The composition of the aromatic polyester resin (A-2) having a carboxyl group on the side chain thus obtained and its characteristic values are shown in Table 2.
[0106] As the aromatic polyester resin (A-3), a high molecular weight polyol (A1-2) is used.
[0107] Production of aromatic polyester resin (A-4) having carboxyl groups on the side chains
[0108] 25 mol parts of maleic acid, 25 mol parts of adipic acid, 50 mol parts of bis(2-hydroxyethyl)terephthalate (BHET), and 0.5 mol parts of scandium trifluoromethanesulfonate were added to a 50 ml glass conical flask equipped with a stirrer, and homogenized at 100°C. After the raw materials were dissolved, the pressure in the system was slowly reduced to 5 mmHg over 30 minutes, and then polycondensation reaction was carried out at 110°C for 4 hours under a vacuum of 0.3 mmHg or less, and then the contents were taken out and cooled. Thereafter, an aromatic polyester resin (A-4) having carboxyl groups at multiple points on the side chain was prepared by Michael addition of the double bond site of maleic acid to the mercapto group of thioglycolic acid. The composition of the obtained aromatic polyester resin (A-4) having carboxyl groups on the side chain is shown in Table 3.
[0109] Production of aromatic polyester resin (A-5) having carboxyl groups on the side chains
[0110] Aromatic polyester resin (A-5) having a carboxyl group on the side chain was synthesized in the same manner as the aromatic polyester resin (A-4) having a carboxyl group on the side chain, but with the addition ratio changed, and the same evaluation as the aromatic polyester resin (A-4) having a carboxyl group on the side chain was performed. The evaluation results are shown in Table 3.
[0111] Synthesis Example of Aromatic Polyester Resin Having Carboxyl Groups on Side Chains (A-6)
[0112] In a reaction vessel equipped with a stirrer, a thermometer, and a reflux tube, 70 parts of a high molecular weight polyol (A1-4), 30 parts of a high molecular weight polyol (A1-2), 2.5 parts of pyromellitic anhydride, and 100 parts of toluene were added, and the mixture was dissolved in toluene while slowly heating to 80°C. After the dissolution was completed, 0.05 parts of triethylamine as a reaction catalyst was added, and the mixture was slowly heated to 105°C to react for 24 hours. After the completion of the reaction was confirmed by IR, the mixture was diluted with 54 parts of toluene to obtain a solution having a solid content concentration of 40% of an aromatic polyester resin (A-6) having a carboxyl group on the side chain. The composition of the aromatic polyester resin (A-6) having a carboxyl group on the side chain thus obtained and its characteristic values are shown in Table 2.
[0113] Synthesis Example of Aromatic Polyester Resin Having Carboxyl Groups on Side Chains (A-7)
[0114] In a reaction vessel equipped with a stirrer, a thermometer, and a reflux tube, 80 parts of a high molecular weight polyol (A1-5), 20 parts of a polycarbonate diol "T5652" manufactured by Asahi Kasei Corporation, 2.8 parts of pyromellitic anhydride, and 100 parts of toluene were added, and the mixture was dissolved in toluene while slowly heating up to 80°C. After the dissolution was completed, 0.05 parts of triethylamine as a reaction catalyst was added, and the mixture was slowly heated up to 105°C to react for 24 hours. After the completion of the reaction was confirmed by IR, the mixture was diluted with 54 parts of toluene to obtain a solution having a solid content concentration of 40% of an aromatic polyester resin (A-7) having a carboxyl group on the side chain. The composition of the aromatic polyester resin (A-7) having a carboxyl group on the side chain thus obtained and its characteristic values are shown in Table 2.
[0115] [Table 2]
[0116]
[0117] [Table 3]
[0118]
[0119] <Number average molecular weight (Mn)>
[0120] The sample [polymer polyol (A1-1 to A1-5), aromatic polyester resin with carboxyl groups on the side chain (A-1 to A-7)] was dissolved or diluted in tetrahydrofuran to a sample concentration of about 0.5 mass %, and filtered using a polytetrafluoroethylene membrane filter with a pore size of 0.5 μm as a sample for measurement. The number average molecular weight was measured by gel permeation chromatography (GPC) using tetrahydrofuran as the mobile phase and a differential refractometer as the detector. The flow rate was 1 ml / min, and the column temperature was 30°C. The chromatographic columns used were KF-802, 804L, and 806L manufactured by Showa Denko. Monodisperse polystyrene was used as a molecular weight standard. However, when the sample was insoluble in tetrahydrofuran, N,N-dimethylformamide was used instead of tetrahydrofuran. Low molecular weight compounds (oligomers, etc.) with a number average molecular weight of less than 1000 were not counted and were simply omitted.
[0121] <Acid value>
[0122] 0.2 g of the sample [polymer polyols (A1-1 to A1-5), aromatic polyester resins having carboxyl groups on the side chains (A-1 to A-7)] was dissolved in 20 ml of chloroform, and titrated with 0.1 N potassium hydroxide ethanol solution using phenolphthalein as an indicator. From the titrated amount, the mg of KOH consumed in neutralization was converted to the amount per 1 g of resin to calculate the acid value (mgKOH / g).
[0123] <Number of carboxyl groups>
[0124] The number of carboxyl groups can be calculated by the following method. For example, when the acid value result is A (mgKOH / g), since the molecular weight of KOH is 56.1g / mol, the molar number of carboxyl groups per 1g of the aromatic polyester resin (A) having carboxyl groups on the side chains can be expressed as A / 56.1 (mmol / g). When the number average molecular weight of the aromatic polyester resin (A) having carboxyl groups on the side chains is B (g), the carboxyl groups in the polymer can be expressed as A / 56.1×B / 1000 (mol), which is used as the number of carboxyl groups per polymer chain (N). COOH ).
[0125] <Glass transition temperature>
[0126] Using a differential scanning calorimeter "DSC220" manufactured by Seiko Instruments, 5 mg of the sample [polymer polyol (A1-1 to A1-5), aromatic polyester resin with carboxyl groups on the side chain (A-1 to A-7)] was placed in an aluminum pan, sealed with a lid, kept at 250°C for 5 minutes, and then quickly frozen with liquid nitrogen, and then heated from -100°C to 300°C at a heating rate of 20°C / min for measurement. The inflection point of the obtained curve was taken as the glass transition temperature.
[0127] Example 1
[0128] A crosslinked aromatic polyester resin composition in the form of a film (hereinafter referred to as a crosslinked aromatic polyester resin film) was prepared as follows.
[0129] 50 mol parts of 1,4-butanediol diglycidyl ether as an epoxy compound (B) were dissolved in NMP (N-methyl-2-pyrrolidone) at a ratio of carboxyl group / epoxy group = 1 / 1 (number of functional groups) per 100 mol parts of carboxyl groups of an aromatic polyester resin (A-1) having carboxyl groups on the side chains, and then 20 mol parts of an ester exchange catalyst Zn(OAc) were dissolved separately. 2 to NMP (N-methyl-2-pyrrolidone). The two solutions were mixed in a Teflon (registered trademark) mold and heated to 40°C to evaporate and remove the solvent. A cross-linked aromatic polyester resin film (thickness 0.7 mm) was obtained by heating the mixed sample at 140°C for 3 hours. The results are shown in Table 4.
[0130] Examples 2 to 8, Comparative Examples 1 to 5
[0131] The aromatic polyester resin (A-1) having a carboxyl group on the side chain and the epoxy compound (B) were changed to the compounds shown in Table 4. The same method as in Example 1 was followed, and the mixing amounts were changed to those shown in Table 4 to carry out Examples 2 to 8 and Comparative Examples 1 to 5. The results are shown in Table 4.
[0132] The epoxy compounds (B) used in Table 4 are the following compounds.
[0133] "jER630" (trade name) manufactured by Mitsubishi Chemical Corporation (triglycidyl p-aminophenol)
[0134] Multifunctional epoxy compound "TETRAD-X" (trade name) manufactured by Mitsubishi Chemical Corporation (N,N,N',N'-tetraglycidyl-m-xylenediamine)
[0135] (Absorbance measurement by infrared spectrophotometry)
[0136] The infrared absorption spectrum of the cross-linked aromatic polyester resin film obtained was measured by the ATR method (total reflection measurement method) under the following conditions using the "Cary 660FTIR" manufactured by Agilent Technologies. The cumulative number of measurements was 16. The infrared absorption spectrum was measured at 1730±10 cm -1 The value of the maximum absorption peak height in the region of 1730 cm-1 is derived from the ester bond. -1 The absorbance near 1730 ), with a range of 3200 to 3600 cm -1 The absorption peak height value of the maximum absorption in the vicinity is 3200 to 3600 cm-1, which is derived from the hydroxyl group. -1The absorbance near 3200~3600 ). It should be noted that the baseline is the valley connecting both sides of each maximum absorption peak. The absorbance ratio is calculated from the obtained absorbance by the following formula.
[0137] (Absorbance ratio) = A 3200~3600 / A 1730
[0138] In Table 4, it is shown that at 1730±10cm -1 The absorption peak with maximum absorption in the region is located at 3200-3600 cm -1 The peak position of the absorption peak with maximum absorption in the region.
[0139] [Table 4-1]
[0140]
[0141] [Table 4-2]
[0142]
[0143] [Table 4-3]
[0144]
[0145] (Softening temperature)
[0146] The softening temperature was obtained by using the "TMA7100" manufactured by HITACHI from the inflection point of the change in the linear expansion coefficient of the sample from room temperature to 300°C. The measurement was carried out in a nitrogen atmosphere under a slight tension (30mN) to prevent the sample from bending. It should be noted that the initial distance between the clamps was 15mm. When the inflection point can be observed, the corresponding temperature is recorded, and when the inflection point is not observed, it is recorded as "-".
[0147] (Self-adhesive)
[0148] Two cross-linked aromatic polyester resin films (4 mm wide × 2 cm long × 0.7 mm thick) were overlapped at the same end, and a temperature above the softening temperature, a pressure of 400 kPa, and a pressing time of 2 hours were used to prepare a two-layer cross-linked aromatic polyester resin film. The two-layer stacked parts were bonded to each other, and self-adhesiveness was ○, and self-adhesiveness was × if they were not bonded.
[0149] (Reformability)
[0150] After a cross-linked aromatic polyester resin film (4 mm wide × 2 cm long × 0.7 mm thick) is spirally wound on a spatula, both ends of the film are fixed to the spatula with tape and subjected to a heat treatment process. As a heat treatment process, it is placed at a high temperature (softening temperature + about 20°C) for 2 hours and then cooled to room temperature. After cooling, the deformed cross-linked polyester resin film is removed from the spatula. When removed from the spatula, if the deformed cross-linked polyester resin film maintains the rolled-up state, it is reformable ○, and if it cannot maintain the rolled-up state and returns to its original flat state, it is reformable ×. In addition, if a part of the cross-linked aromatic polyester resin film is dissolved and cannot be evaluated, it is recorded as "-".
[0151] (Damage repair)
[0152] A wound (depth of about 0.1 mm) was made on the surface of a cross-linked aromatic polyester resin film (1.5 cm long × 1.5 cm wide × 0.7 mm thick) with a cutter. Afterwards, the cross-linked aromatic polyester resin film was subjected to a heat treatment process. As a heat treatment process, it was placed at a high temperature (softening temperature + about 20°C) for 10 minutes, and then cooled to room temperature. After the heat treatment process, when the wound disappears and the cross-linked aromatic polyester resin film becomes a surface-free wound, the damage repair property (self-repair property) is ○, and when the wound remains, the damage repair property (self-repair property) is ×. In addition, when a part of the cross-linked aromatic polyester resin film is dissolved and cannot be evaluated, it is recorded as "-".
[0153] (5% weight loss temperature)
[0154] The measurement was performed using a thermal analyzer "DTG-60" manufactured by Shimadzu Corporation. 10 g of a sample (cross-linked aromatic polyester resin film) was placed in an aluminum pan, and the weight loss was measured when the temperature was raised from room temperature to 400°C at a rate of 5°C / min. The temperature at which the weight was reduced by 5% (5% weight loss temperature) was used as an indicator of heat resistance.
[0155] (90° peel strength)
[0156] A test piece of 20 mm long x 50 mm wide was cut out from the obtained cross-linked aromatic polyester resin film (thickness 0.7 mm). The cut test piece was placed on a PET film (manufactured by Toyobo Co., Ltd.) with a thickness of 25 μm, and the same type of PET film was placed on the test piece to form a three-layer structure of "PET film / cross-linked aromatic polyester resin film / PET film". The layers were bonded in a hot press by applying pressure and heating at 170°C, 2 MPa, and 280 seconds. The laminated body obtained by bonding was used as a sample for 90° peel strength evaluation.
[0157] In addition, a polyimide film (PI, "apical" (registered trademark) manufactured by Zhonghua Company, with a thickness of 12.5 μm) was used instead of the above-mentioned PET film, and a 90° peel strength evaluation sample was prepared under the same conditions, except that it was constituted as a three-layer structure of "PI / cross-linked aromatic polyester resin film / PI". It should be noted that for the cross-linked aromatic polyester resin films obtained in Examples 5 and 6, samples prepared by changing the heating temperature of the hot press to 200°C were also prepared.
[0158] In addition, a rolled copper foil (thickness 20 μm) and a polyimide film (PI, "apical" (registered trademark) manufactured by Kaneka Co., Ltd., thickness 12.5 μm) were used instead of the above-mentioned PET film, except that a three-layer structure of "Cu / crosslinked aromatic polyester resin film / PI" was formed, and a 90° peel strength evaluation sample was prepared under the same conditions. In addition, regarding the crosslinked aromatic polyester resin films obtained in Examples 5 and 6, samples prepared by changing the heating temperature of the hot press to 200°C were also prepared.
[0159] The 90° peel strength was measured at 25°C and a tensile speed of 50 mm / min using Autograph AG-Xplus manufactured by Shimadzu Corporation. Based on the measured 90° peel strength, the adhesiveness of the film was evaluated according to the following criteria. The evaluation results are shown in Table 5 below. Note that "-" means not implemented.
[0160] <Evaluation Criteria>
[0161] ◎: 1.0N / mm or more
[0162] ○: 0.5N / mm or more, less than 1.0N / mm
[0163] △: 0.35N / mm or more, less than 0.5N / mm
[0164] ×: less than 0.35N / mm
[0165] (Formability)
[0166] The obtained cross-linked aromatic polyester resin film (thickness 0.7mm) was cut into samples of 5mm width × 5mm length and inserted into a mold. The mold was made by cutting out a circle with a diameter of 8mm on a Teflon (registered trademark) sheet with a thickness of 1mm. Then, pressure and heating were applied using a hot press. The pressurization conditions were 4MPa, and the heating conditions were softening temperature +30°C for 15 minutes. When the cross-linked aromatic polyester resin film sheet can be formed into the shape of the mold, the formability is evaluated as ○, and when it cannot be formed, the formability is evaluated as ×. The evaluation results are shown in Table 5 below. It should be noted that "-" means not implemented.
[0167] (Extrusion moldability)
[0168] 6 g of the obtained cross-linked aromatic polyester resin film (thickness 0.7 mm) was cut into samples of 5 mm width × 5 mm length, and fed into a twin-screw extruder "MiniLab" manufactured by HAAKE at a barrel temperature of 150° C. in three portions and extruded at a screw speed of 50 min. -1 After the sample was added, the kneaded product was kneaded for 5 minutes and then extruded from the barrel. After kneading, if the kneaded product could be discharged and a linear molded body was obtained, it was evaluated as ○, and if the kneaded product could not be discharged and a linear molded body could not be obtained, it was evaluated as ×. The evaluation results are shown in Table 5 below. It should be noted that "-" means that it was not implemented.
[0169] (Solder heat resistance)
[0170] The obtained crosslinked aromatic polyester resin film was bonded to the smooth surface of rolled copper foil of a 49 μm thick copper-clad laminate (ESPANEX series, Cu / polyimide / Cu=12 μm / 25 μm / 12 μm, manufactured by Nippon Steel Chemical & Materials Co., Ltd.). 2 The laminated sample for solder heat resistance evaluation was obtained by pressing for 280 seconds under pressure of , and the softening temperature of the cross-linked aromatic polyester resin film was above 150°C. When the film was not sufficiently bonded at the pressing temperature of 170°C, the pressing temperature was increased to 180°C or 200°C to prepare a laminated sample. A 2.0 cm × 2.0 cm test piece was cut from the obtained laminated sample, and the test piece was floated for 1 minute in a solder bath whose bath temperature was adjusted from 250°C to 280°C in units of 10°C, and the upper limit temperature at which no expansion occurred was measured. That is, the test piece was floated in a solder bath with a bath temperature of 250°C for 1 minute. When no expansion occurred, the test piece was floated in a solder bath with a bath temperature of 260°C, 270°C or 280°C for 1 minute, and the operation was repeated until expansion occurred, and the upper limit temperature at which no expansion occurred was measured. The measurement results are shown in Table 5 below. The higher the upper limit temperature at which no expansion occurs, the better the solder heat resistance. In addition, regarding Example 5 and Example 6, the solder heat resistance was evaluated for the sample produced at a pressing temperature of 170° C. and the sample produced at a pressing temperature of 200° C., respectively.
[0171] (Room temperature storage stability)
[0172] The room temperature storage stability of the obtained cross-linked aromatic polyester resin film was evaluated based on the change rate of the gel fraction and the softening behavior.
[0173] (1) Change rate of gel fraction
[0174] First, the gel fraction of the obtained crosslinked aromatic polyester resin film was measured. The gel fraction was measured by the following method.
[0175] 0.125 g of the obtained crosslinked aromatic polyester resin film was weighed and immersed in 25 ml of methyl ethyl ketone at room temperature for 2 hours, and then dried at 80°C for 1 hour using a vacuum dryer to measure the mass of the remaining gel component. The gel fraction was determined by the following formula.
[0176] Gel fraction (%) = (weight of residual gel component after drying / 0.125) × 100
[0177] Next, the crosslinked aromatic polyester resin film was stored at a fixed temperature of 5°C, 25°C or 40°C for 6 months, and the gel fraction was measured by the above method after 6 months. Based on the gel fraction at the beginning of storage and the gel fraction after 6 months of storage, the change rate of the gel fraction from the beginning of storage was calculated. The change rate is the absolute value of the difference in gel fraction (%) before and after 6 months as shown in the following formula.
[0178] Change rate = gel fraction after 6 months of storage (%) - gel fraction at the beginning of storage (%)
[0179] When the change rate was less than 10%, it was evaluated as ○, when the change rate was 10% or more and 25% or less, it was evaluated as △, and when the change rate exceeded 25%, it was evaluated as ×. The evaluation results are shown in Table 5 below. Note that "-" means that it was not implemented.
[0180] (2) Softening behavior
[0181] After the obtained cross-linked aromatic polyester resin film was stored at 25°C for 6 months, the presence or absence of softening behavior based on the bond exchange reaction was evaluated by stress relaxation measurement. For the stress relaxation measurement, MCR302 (manufactured by Anton Paar) was used to perform stress relaxation tests at temperatures of 100°C, 150°C, and 180°C. The test was performed in a nitrogen atmosphere. A disc-shaped material with a diameter of 8 mm and a thickness of 0.7 mm cut out from the above cross-linked aromatic polyester resin film was used as the test piece.
[0182] After storage at 25°C for 6 months, if the stress relaxation test at any temperature of 100°C, 150°C, or 180°C showed softening behavior, the evaluation was ○; if the stress relaxation test at any temperature of 100°C, 150°C, or 180°C showed no softening behavior, the evaluation was ×. The evaluation results are shown in Table 5 below. If stress relaxation is shown after storage at 25°C for 6 months, it means that the softening characteristics based on bond exchange are maintained after storage, and there is no initial behavior and change during long-term storage at room temperature.
[0183] (Solvent resistance)
[0184] The obtained cross-linked aromatic polyester resin film (thickness 0.7mm) was cut into samples of 5mm width × 5mm length, and one sample was put into each screw bottle. Three bottles were prepared for each standard, and 3ml of ethanol, dimethylformamide (DMF) or tetrahydrofuran (THF) was added respectively, and the samples were left standing at room temperature for 5 hours. After standing for 5 hours, if there was no change compared with before immersion, it was evaluated as good solvent resistance ◎, if swelling of the sample was observed but it was not dissolved, it was evaluated as solvent resistance ○, and if it was dissolved, it was evaluated as no solvent resistance ×. The evaluation results are shown in Table 5 below. It should be noted that "-" means that it was not implemented.
[0185] (90° peel strength when heated)
[0186] The 90° peel strength during heating is measured for the "Cu / cross-linked aromatic polyester resin film / PI" in the above-mentioned 90° peel strength evaluation sample using a thermostatic chamber (manufactured by Shimadzu Corporation, THERMOSTATIC CHAMBER) at the softening temperature of each sample recorded in Table 5 + 30°C. For the measurement of the 90° peel strength, an autograph AG-Xplus manufactured by Shimadzu Corporation was used to measure at the softening temperature of each sample + 30°C at a tensile speed of 50 mm / min. Based on the measured 90° peel strength during heating, the peelability of the laminate was evaluated according to the following criteria. The evaluation results are shown in the following Table 5. It should be noted that "-" means not implemented.
[0187] <Evaluation Criteria>
[0188] ◎: Less than 0.35N / mm
[0189] ○: 0.35N / mm or more, less than 0.5N / mm
[0190] △: 0.5N / mm or more, less than 1.0N / mm
[0191] ×: 1.0N / mm or more
[0192] The cross-linked aromatic polyester resin film obtained in Example 1 was cut into thin resin shapes (5 mm wide × 5 mm long × 0.7 mm thick), melted at a temperature of 200°C, and discharged into cooling water at a single hole discharge rate of 1.0 g / min through circular solid small holes (orifices) with an aperture of 1.0 mm arranged at intervals of 4 mm on the effective surface of a nozzle with a width of 40 cm and a length of 4 cm, and solidified. In detail, cooling water was arranged 10 cm below the discharge position, and a pair of traction conveyors with a width of 50 cm were arranged in parallel at intervals of 3 cm to be partially exposed on the water surface, thereby pulling, while the contact parts were welded, the two sides were sandwiched, and it was introduced into the cooling water at a speed of 1.0 m per minute to solidify. Then, after drying in a hot air dryer at 70°C for 15 minutes, it was cut into a specified size. As a result, a film with a thickness of 3 cm and a density of 0.060 g / cm 3 The mesh structure.
[0193] [Table 5-1]
[0194]
[0195] [Table 5-2]
[0196]
[0197] [Table 5-3]
[0198]
[0199] Embodiment 1, 3, 4
[0200] The cross-linked aromatic polyester resin films of Examples 1, 3, and 4 are systems in which 50 mol parts of epoxy compound (B) (carboxyl group / epoxy group = 1 / 1 (number of functional groups) relative to 100 mol parts of carboxyl groups) of the polyester resins (A-1, A-2, and A-4) and 20 mol parts of zinc acetate are mixed. The films exhibit softening, self-adhesiveness, re-formability, and damage repairability based on ester bond exchange.
[0201] Example 2
[0202] The crosslinked aromatic polyester resin film of Example 2 is a system in which the zinc acetate used in Example 1 is reduced from 20 mol parts to 10 mol parts, and the softening temperature rises from 120° C. to 150° C. This is considered to be due to the small amount of added ester exchange catalyst, which reduces the ester exchange activity.
[0203] Embodiment 5, 6
[0204] A system in which a trifunctional epoxy or a tetrafunctional epoxy as the epoxy compound (B) is mixed with the same polyester resin (A-1) as in Example 1, and the ratio of carboxyl group / epoxy group is 1 / 1 (number of functional groups) relative to 100 mol parts of carboxyl groups in the polyester resin (A-1), and the softening temperature is increased by 50°C or more compared with that in Example 1. It can be confirmed that the softening temperature tends to increase as the crosslinking density of the obtained crosslinked aromatic polyester resin film increases.
[0205] Embodiment 7, 8
[0206] The cross-linked aromatic polyester resin films of Examples 7 and 8 are systems in which 50 mol parts of epoxy compound (B) (carboxyl group / epoxy group = 1 / 1 (number of functional groups) relative to 100 mol parts of carboxyl groups) of polyester resins (A-6 and A-7) and 20 mol parts of zinc acetate are mixed. The films exhibit softening, self-adhesiveness, re-formability, damage repairability, and heat resistance based on ester bond exchange.
[0207] The crosslinked aromatic polyester resin films of Examples 1 to 8 have a large 90° peel strength and are useful as adhesives. They are also excellent in formability, extrusion formability, solder heat resistance, room temperature storage stability, and solvent resistance. In addition, it was found that the 90° peel strength when heated to the softening temperature + 30°C was small and they were easy to peel.
[0208] Comparative Example 1
[0209] The polyester resin (A-3) has a polymer structure without carboxyl groups on the side chains. Since carboxyl groups exist only at the terminals, three-dimensional crosslinking cannot be performed, and physical properties cannot be evaluated.
[0210] Comparative Example 2
[0211] The cross-linked aromatic polyester resin composition using a polyester resin (A-5) having a very high acid value has a high absorbance ratio, and the softening temperature and the 5% weight loss temperature are almost the same. It is believed that the cross-linked aromatic polyester resin decomposes near the softening temperature. The high absorbance ratio of the cross-linked aromatic polyester resin composition means that the number of secondary OH groups generated by the reaction between the carboxyl group and the epoxy group of the polymer side chain is large. In short, it is believed that because the cross-linking density of the cross-linked aromatic polyester resin composition is very high, the molecules themselves are difficult to move, and ester exchange is difficult to occur.
[0212] Comparative Examples 3, 4, and 5
[0213] This is a system without an ester exchange catalyst (zinc acetate) in Examples 1, 5, and 6. When only an aromatic polyester resin having a carboxyl group on the side chain and an epoxy compound are mixed and cured, a crosslinking reaction proceeds, but an ester exchange reaction at high temperature does not proceed, and no softening behavior at high temperature, self-adhesion, re-formability, or damage repairability is exhibited. This is considered to be a general thermosetting polyester resin.
[0214] Possibility of Industrial Application
[0215] The crosslinked aromatic polyester resin composition of the present invention has heat resistance of 230°C or higher (especially 300°C or higher) and is excellent in self-adhesiveness, reshaping properties, and damage repair properties in a temperature range above the softening temperature. Therefore, it is particularly useful as a reusable adhesive and coating.
Claims
1. A cross-linked aromatic polyester resin composition, characterized in that: The invention comprises a crosslinked aromatic polyester resin (C) and an ester exchange catalyst (D), and satisfies the following (1) to (2), wherein the molar ratio of the ester exchange catalyst (D) to the carboxyl groups contained in the aromatic polyester resin (A) having carboxyl groups on the side chains, i.e., the ratio of carboxyl groups to the ester exchange catalyst is 100:10 to 100:
40. (1) The cross-linked aromatic polyester resin (C) is a reaction product of an aromatic polyester resin (A) having a carboxyl group on a side chain and an epoxy compound (B); (2) When the cross-linked aromatic polyester resin composition is measured by infrared spectrophotometry, the wave number derived from the hydroxyl group is 3200 to 3600 cm -1 The peak absorbance A near 3200~3600 The wave number relative to the ester bond is 1730 cm -1 The peak absorbance A near 1730 The ratio of A 3200~3600 / A 1730 It is greater than 0.005 and less than 0.
038.
2. The cross-linked aromatic polyester resin composition according to claim 1, wherein The acid value of the aromatic polyester resin (A) having a carboxyl group on the side chain is 5 mgKOH / g or more and 120 mgKOH / g or less.
3. The crosslinked aromatic polyester resin composition according to claim 1 or 2, wherein The number average molecular weight of the aromatic polyester resin (A) having a carboxyl group on a side chain is 8,000 or more.
4. The crosslinked aromatic polyester resin composition according to claim 1 or 2, wherein The molar ratio of the epoxy group contained in the epoxy compound (B) to the carboxyl group contained in the aromatic polyester resin (A) having a carboxyl group on the side chain, that is, the carboxyl group:epoxy group, is 100:50 to 100:
150.
5. The crosslinked aromatic polyester resin composition according to claim 1 or 2, wherein The number average molecular weight of the epoxy compound (B) is 100 or more and 500 or less.
6. A method for producing a crosslinked aromatic polyester resin composition, comprising the steps of mixing an aromatic polyester resin (A) having a carboxyl group on a side chain and having an acid value of 5 mgKOH / g to 120 mgKOH / g, an epoxy compound (B) and an ester exchange catalyst (D), and heating to crosslink the mixture. When the cross-linked aromatic polyester resin composition is measured by infrared spectrophotometry, the wave number of the hydroxyl group is 3200-3600 cm -1 The peak absorbance A near 3200~3600 The wave number relative to the ester bond is 1730 cm -1 The peak absorbance A near 1730 The ratio of A 3200~3600 / A 1730 It is greater than 0.005 and less than 0.
038. 7 . A self-adhesive comprising the cross-linked aromatic polyester resin composition according to claim 1 .
8. A self-repairing material, characterized in that: Contains a crosslinked aromatic polyester resin (C) and an ester exchange catalyst (D), and satisfies the following (1) to (2), (1) The cross-linked aromatic polyester resin (C) is a reaction product of an aromatic polyester resin (A) having a carboxyl group on a side chain and an epoxy compound (B); (2) When the cross-linked aromatic polyester resin composition is measured by infrared spectrophotometry, the wave number derived from the hydroxyl group is 3200 to 3600 cm -1 The peak absorbance A near 3200~3600 The wave number relative to the ester bond is 1730 cm -1 The peak absorbance A near 1730 The ratio of A 3200~3600 / A 1730 It is greater than 0.005 and less than 0.
038.
9. The self-healing material according to claim 8, wherein: The acid value of the aromatic polyester resin (A) having a carboxyl group on the side chain is 5 mgKOH / g or more and 120 mgKOH / g or less.
10. The self-healing material according to claim 8 or 9, wherein: The number average molecular weight of the aromatic polyester resin (A) having a carboxyl group on a side chain is 8,000 or more.
11. The self-healing material according to claim 8 or 9, wherein: The molar ratio of the epoxy group contained in the epoxy compound (B) to the carboxyl group contained in the aromatic polyester resin (A) having a carboxyl group on the side chain, that is, the carboxyl group:epoxy group, is 100:50 to 100:
150.
12. The self-healing material according to claim 8 or 9, wherein: The number average molecular weight of the epoxy compound (B) is 100 or more and 500 or less.
13. The self-healing material according to claim 8 or 9, wherein: The molar ratio of the transesterification catalyst (D) to the carboxyl groups contained in the aromatic polyester resin (A) having carboxyl groups on the side chains, that is, carboxyl groups: transesterification catalyst, is 100:10 to 100:
40.
14. A forming material, characterized in that: Contains a crosslinked aromatic polyester resin (C) and an ester exchange catalyst (D), and satisfies the following (1) to (2), (1) The cross-linked aromatic polyester resin (C) is a reaction product of an aromatic polyester resin (A) having a carboxyl group on a side chain and an epoxy compound (B); (2) When the cross-linked aromatic polyester resin composition is measured by infrared spectrophotometry, the wave number derived from the hydroxyl group is 3200 to 3600 cm -1 The peak absorbance A near 3200~3600 The wave number relative to the ester bond is 1730 cm -1 The peak absorbance A near 1730 The ratio of A 3200~3600 / A 1730 It is greater than 0.005 and less than 0.
038.
15. The forming material according to claim 14, wherein The acid value of the aromatic polyester resin (A) having a carboxyl group on the side chain is 5 mgKOH / g or more and 120 mgKOH / g or less.
16. The forming material according to claim 14 or 15, wherein The number average molecular weight of the aromatic polyester resin (A) having a carboxyl group on a side chain is 8,000 or more.
17. The forming material according to claim 14 or 15, wherein The molar ratio of the epoxy group contained in the epoxy compound (B) to the carboxyl group contained in the aromatic polyester resin (A) having a carboxyl group on the side chain, that is, the carboxyl group:epoxy group, is 100:50 to 100:
150.
18. The forming material according to claim 14 or 15, wherein The number average molecular weight of the epoxy compound (B) is 100 or more and 500 or less.
19. The forming material according to claim 14 or 15, wherein The molar ratio of the transesterification catalyst (D) to the carboxyl groups contained in the aromatic polyester resin (A) having carboxyl groups on the side chains, that is, carboxyl groups: transesterification catalyst, is 100:10 to 100:40.
Citation Information
Patent Citations
Resin composition
JP2020023591A
Stator of rotary electric machine
JP2020174488A
Heattsensitive carboxylated copolymer adhesive and its production method
JP1977005849A
Coating composition for coated steel sheet
JP1990142869A